Interventions to improve lung cancer screening among racially and ethnically minoritized groups: A scoping review. (February 2023) - Nam, Jason; Krishnan, Govind; Shofer, Scott; Navuluri, Neelima
Highlights: It is well-established that there are disparities in lung cancer screening for ethnic and racial minorities. Interventions to improve these disparities have been limited in the United States, though multiple have been described in the last five years. Interventions can be categorized as at an individual patient-level, at a clinic or institution-level, or at a community-level. Clinic-level interventions focused on streamlining the process have shown the greatest improvement in screening as measured by number of patients who underwent low-dose CT scans. Community-level interventions have the most flexibility to tailor screening efforts to target recruitment of racial and ethnic minorities. Abstract: Lung cancer screening (LCS) decreases lung cancer related mortality among high-risk people who smoke cigarettes and has been endorsed by the US Preventive Services Task Force (USPSTF) since 2013. However, adoption of LCS has been limited, and disparities in LCS among racially and ethnically minoritized groups have become apparent. While recommendations to improve disparities in LCS have been made, there is a lack of information on how these recommendations have been implemented and their relative effectiveness in improving screening disparities. This scoping review addresses this knowledge gap by examining interventions that have been implemented to improve LCS among racially and ethnically minoritized groups in the United States. A comprehensive search of MEDLINE (via PubMed), EMBASE (via Elsevier), CINAHL Complete (via EBSCO), and Scopus (via Elsevier), for articles from the period 1 January 2010 through 22 October 2021 was completed. Out of 17, 045 references screened, only 11 studies describing an intervention to improve disparities in LCS were identified, underscoring the dearth of data on established interventions. The interventions discussed could be categorized into three groups -- patient level (n = 3), clinic/institution level (n = 3), and community level (n = 5) interventions. Of those studies reporting effectiveness data (n = 8), there was substantial heterogeneity in the outcomes measured and their relative effectiveness. We found that interventions which streamlined the LCS process at the level of a single clinic or institution were the most effective in improving LCS. Community-level interventions that focused on engagement and education had the greatest potential to target racially and ethnically minoritized groups. Our study underscores the need for more robust research on addressing barriers to LCS by identifying effective patient, clinic, and community-level interventions to improve LCS disparities and the need for potential standardization of intervention effectiveness outcomes.